Islamic Leadership Behaviour Practices among Muslim Women Managers - Mahazan Abdul Mutalib @ Talib; Nurhafizah Mohd. Sukor; Khairunneezam Mohd Noor; Wan Mohd Fazrul Azdi Wan Razali; Siti Aishah Hussin; Rozita Abdullah (HRMARS, 2024)
Indexed by ERA